Sisters in Toil: The Progressive Devaluation and Defeminization of Ontario Dairywomen's Work and Tools 1813-1914 - Quaile, Meredith Leigh (Memorial University, 2010)
In nineteenth and early-twentieth century Ontario, dairywomen toiled daily with cows and manure, sour milk and greasy butter, yet without improved apparatus, agricultural education, or male support. On the provincial family farm, milking, cream-separating, and butter-making chores included various time-consuming steps, physical labour, and an array of task-specific objects. This thesis analyses agriculture, and dairying in specific, as it began the transition from traditional to industrial, and consequently from female to male. – This dissertation touches on particular topics relevant to farmwomen's labour, including: agricultural education and improvement through science; public debate and perception surrounding gendered work; the government's role in promoting industrialization and thus defeminization; the concept of the dairyqueen in technological advertising; and, in particular, real farmwomen. These dairying 'sisters' include the well known, like Susanna Moodie and Catharine Parr Traill, Laura Rose, and Eliza Jones, and the unknown, such as Mary Newsam and the Hallen sisters, while focusing on Lamira Billings and her daughters Sabra and Sally. – This qualitative study reveals that by employing common dairy tools as a dominant, primary source, there are alternative perspectives from which to consider rural women's experiences. Analysis of material culture objects, like milking stools and pails, butter bowls and scotch hands, shallow separating pans and tin creamer cans, also allows for exploration of the tensions between projected male ideals and tangible female work - a question central to understanding gender and labour within a social history context. In addition to technologies, sources like The Farmer's Advocate, the photographs of Reuben Sallows, and early dairy advertisements, add to our understanding of the concerns surrounding dairywomen's labour during the period discussed. – Historians have suggested that dairy work was removed from the female sphere before the turn of the twentieth century in Ontario. Male agriculture authorities, scientific experts, and government officials, indeed initiated a conscious devaluation of farmwomen's work, oriented toward the defeminization of dairying. Rather than being removed from dairy work, however, Ontario's farmwomen continued separating cream and making butter between 1813 and 1914, habitually and simply equipped with their two hands, their mother's knowledge, and their grandmother's tools.